One step ahead. - Gorelik, Vlad (New York ACM, 2007)
Security vulnerabilities abound, but a few simple steps can minimize your risk.
Keywords: Computing Milieux; Management of Computing and Information Systems; Security and protection (e.g. firewalls).; Computer Systems Organization; Computer Communication Networks; Software; Operating Systems; Design; Management; Security